A Case Study on the Administrative Impacts of Different Engineering Capstone Teaching Modalities - Justin L. Lapp; Andrew Goupee; Wilhelm A. Friess (MDPI AG, 2023)
The capstone experience in engineering curriculums is a critical component focused on the unification of several years of student learning, but its unique nature can present challenges to engineering departments in faculty assignment and ensuring consistent, high-quality instruction. During a seven-year period, five instructional modalities, defining the interaction between students and faculty, were explored in capstone courses in the University of Maine Mechanical Engineering Department. By sharing the lessons learned from this case study, other engineering departments can make more informed decisions about how to operate capstone courses. We present the benefits and challenges of each modality and evaluate them for scalability, student satisfaction, project diversity, cost, and instructor workload. Annual data were collected on student, instructor, and project counts. Data from student evaluations and department budgets were used to evaluate student satisfaction and costs, respectively. Insights from the three authors, who were the primary capstone instructors during this study, are shared as part of the evaluations and lessons learned. Key results are that cost, student satisfaction, and project diversity did not depend strongly on the teaching modality. However, scalability and instructor workload were highly dependent on the teaching modality. The University of Maine Mechanical Engineering Department sees the most promise in a modality with multiple lead instructors who each oversee a portion of the teams, which provides scalability to add or remove instructors, and the ability for high-quality instruction through close coordination of a small instructor group.